Electrical Detection and Magnetic Imaging of Stabilized Magnetic Skyrmions in Fe1−xCoxGe (x < 0.1) Microplates - Stolt, Matthew J.; Schneider, Sebastian; Mathur, Nitish; Shearer, Melinda J.; Rellinghaus, Bernd; Nielsch, Kornelius; Jin, Song (Advanced Functional Materials, 2019)
Magnetic skyrmions are topologically protected spin textures that are being investigated for their potential use in next generation magnetic storage devices. Here, magnetic skyrmions and other magnetic phases in Fe 1−x Co x Ge (x < 0.1) microplates (MPLs) newly synthesized via chemical vapor deposition are studied using both magnetic imaging and transport measurements. Lorentz transmission electron microscopy reveals a stabilized magnetic skyrmion phase near room temperature (≈280 K) and a quenched metastable skyrmion lattice via field cooling. Magnetoresistance (MR) measurements in three different configurations reveal a unique anomalous MR signal at temperatures below 200 K and two distinct field dependent magnetic transitions. The topological Hall effect (THE), known as the electronic signature of magnetic skyrmion phase, is detected for the first time in a Fe 1−x Co x Ge nanostructure, with a large and positive peak THE resistivity of ≈32 nΩ cm at 260 K. This large magnitude is attributed to both nanostructuring and decreased carrier concentrations due to Co alloying of the Fe 1−x Co x Ge MPL. A consistent magnetic phase diagram summarized from both the magnetic imaging and transport measurements shows that the magnetic skyrmions are stabilized in Fe 1−x Co x Ge MPLs compared to bulk materials. This study lays the foundation for future skyrmion-based nanodevices in information storage technologies.
CRIS-Team Scopus Importer:2022-04-14
Keywords: anisotropic magnetoresistance; iron germanide; Lorentz transmission electron microscopy; magnetic skyrmion; topological Hall effect